Effect of Seed Priming with Proline on Germination and Seedling Growth of Mungbean under Salt Stress - Sobahan, Muhammad Abdus (South Asian Journal of Agriculture, 2019)
Seed priming is a pre-sowing treatment that enhances germination performance and stress tolerance of germinating seeds. The effect of seed priming with proline on germination and seedling growth of mungbean (Vigna radiata L.) under salt stress was investigated. The experiment carried out in completely randomized design with three replications in May 2018 at the Research Laboratory of the School of Agriculture and Rural Development, Bangladesh Open University, Gazipur, Bangladesh. Salt stress at 5 dSm-1 decreased seed germination percentage, plumule length, radicle length, plumule fresh weight, radicle fresh weight and seed vigour index compared to control. Seed priming with proline increased germination percentage (53.84%), plumule length, radicle length, plumule fresh weight, radicle fresh weight and seed vigour index under salt stress. The results suggested that seed priming with proline could effectively alleviate the inhibitory effects of salt stress on seed germination and seedling growth of mungbean. South Asian J. Agric., 7(1&2): 15-18